Do Effectiveness Board Affect Sustainability Performance? Evidence from Indonesia - Robby Krisyadi; Budi Chandra; Juli Angraini (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Many Indonesian companies struggle with limited board effectiveness and inadequate corporate governance structures, which in turn impede their sustainability performance. Instead of prioritizing sustainability as a strategic goal, most firms in Indonesia view it as just a compliance obligation. The main objective of this study is to analyze the influence of board size, board independence, meeting frequency, and meeting attendance rate on sustainability performance. Information for this research was gathered from the yearly and sustainability reports of firms listed on the Indonesia Stock Exchange between the years 2018 and 2022. Companies that released sustainability reports during this time frame were chosen for the sample using purposive sampling method. The analysis of data utilized the panel regression technique in conjunction with the Eviews tool for analysis. The results from the regression analysis indicate a clear and positive impact of board independence and attendance rate at meetings on sustainability performance. On the other hand, the size of the board and the frequency of meetings do not seem to have a significant impact on sustainability performance. This research can be a reference for future researchers and for companies to evaluate and optimize corporate governance so as to increase transparency and support the achievement of sustainability performance. The novelty of this article lies in the research focus on companies that publish sustainability reports in developing countries, namely Indonesia as a form of transparency of sustainability performance.